SANTRI DAN KONSERVASI LINGKUNGAN (Studi Pandangan Hidup Santri di Kawasan Pegunungan Dieng) - Muhtar Sofwan Hidayat; Fasichul Lisan (Manarul Qur'an: Jurnal Ilmiah Studi Islam, 2018)
Environmental issues are receiving great attention from almost all countries in theworld. But unfortunately until now the rate of environmental damage is stillongoing which resulted in frequent occurrence of natural disasters. Especially inthe Dieng mountains in the last few decades there are frequent landslides andfloods. Environmental damage occurs due to the exploration of natural resourcesto meet the needs of human beings without regard to environmental sustainability.The utilization of the environment without regard to environmental sustainabilityleads to more exploitation that leads to environmental crises and disadvantages thecommunity.In the midst of incessant environmental problems that are increasinglyuncooperative with human beings emerged a caring attitude and interestingresponse that emerged from the santri. Conservation efforts by cultivatingcultivation from potato plant to carica plant begins by some farmers whonotabenenya is dropout pesantren (santri). The concern of santri on theenvironment becomes an interesting phenomenon to be studied. Because invarious parts of the world emerge a series of issues of religious fundamentalism,precisely dieng Dieng Islam comes with a completely different face, they are moreresponsive and enthusiastic to be active in environmental control efforts.Departure from the phenomenon then there are two problems that want to answerresearchers that is how the process of environmental conservation in the mountainarea Dieng? and How the view of life santri Dieng mountainous area thatencourages the conservation of agricultural land? This research usesphenomenology approach to reveal the view of life of santri in Dieng mountains.The result of this research reveals the life view which is used as the foundation bythe santri is hablum minal 'nature so the conservation of the environment is amanifestation of their love to nature, both hubbul Waton minal their faith sees thatlove the homeland part of the faith they manifest by doing environmentalConservation. Third, their awareness as khalifatullah fil ard. Thus, theconservation efforts undertaken by the santri depart from their sense ofresponsibility as the Caliph on earth.